Polymeric Micelles encapsulating Sesbania grandiflora leaf extract on the antibacterial activity of Gram positive and Gram negative bacteria - Ismail, Elysha Nur; Othman, Zulkefley; Sarchio, Seri Narti Edayu (2024)
Diseases caused by pathogenic microorganisms are a rising concern. Resistance, high costs, side effects and low availability of current antibiotics has led researchers to focus on natural products, finding for lead compounds to develop better drugs.